2012
DOI: 10.1007/s00062-012-0182-x
|View full text |Cite
|
Sign up to set email alerts
|

Coiling of Ruptured Tiny Cerebral Aneurysms, Feasibility, Safety, and Durability at Midterm Follow-Up, and Individual Experience

Abstract: Coil embolization of tiny ruptured cerebral aneurysms is feasible. Careful consideration of the technical issues in treatment of such aneurysms is essential to achieve technical success while avoiding complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In our institution, small cerebral aneurysm recurrences with sizes of 7 mm or less that require additional treatment, which was included in the study criteria, were defined as cases where contrast filling of more than 2 mm of the residual aneurysm was observed. It was judged that 2 mm was the minimum size that could be filled using one minimum size coil 12,17,30) . Of the 19 recurrence cases, six cases (31.6%) showed repeated recurrence due to coil mesh compaction even after additional treatment and for this, additional coil embolization was repeatedly performed.…”
Section: Discussionmentioning
confidence: 99%
“…In our institution, small cerebral aneurysm recurrences with sizes of 7 mm or less that require additional treatment, which was included in the study criteria, were defined as cases where contrast filling of more than 2 mm of the residual aneurysm was observed. It was judged that 2 mm was the minimum size that could be filled using one minimum size coil 12,17,30) . Of the 19 recurrence cases, six cases (31.6%) showed repeated recurrence due to coil mesh compaction even after additional treatment and for this, additional coil embolization was repeatedly performed.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of a tiny aneurysm both surgical clipping and endovascular embolization are highly difficult due to their size and thin walls with most presenting with a wide neck [5,15,16] and are also associated with morbidity [17][18][19]. In the case of surgical clipping, the tiny size of the aneurysm makes it difficult to clip firmly.…”
Section: Introductionmentioning
confidence: 99%
“…This has made the use of BACE a more prevalent and preferable approach by clinicians in the last several years to treat wide-necked intracranial aneurysms [3,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21]. Balloons have also been shown to help in the tamponade of the vessel in case of intraoperative perforation [22,23] and are also used for occlusion testing before sacrifice of the vessel. Previously, Lubicz et al [8], Mu et al [15], Youn et al [16] and Cekirge et al [17 ]reported the use of a super-compliant balloon (HyperForm) in the treatment of wide-necked aneurysms located on arterial bifurcations and/or small arteries.…”
Section: Introductionmentioning
confidence: 99%